IMPLEMENTASI KEBIJAKAN PERDAGANGAN MEKSIKO TERHADAP PRODUK KAKI AYAM (CHICKEN LEG QUARTER) ASAL AMERIKA SERIKAT (TAHUN 2011) - Delvi, Fanita; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The U.S is Mexicoâs primary supplier of poultry product, mainly ChickenLeg Quarters (CLQs). The objectives of this study are to describe the trade policyenvironment for imports of CLQs product into the Mexican Market since the nontarifftrade agreements under NAFTA in 1994, and to analyze the impact of antidumpingpolicy mechanism imposed by the Mexican government in 2011.This research uses politic economy theory related to international tradetheory which has been revealed by Heckscher-Ohlin This research is qualitativeresearch which is used by library observation.The result of this research prove that there some factors that encougareMexican impose of anti-dumping duties on U.S Chicken Leg Quarters (CLQs),that author classified in: 1) Mexican poultry has become the fastest growingsector in the livestock industry category in Mexico; 2) modernization; 3) poultryindustry becomes source of jobs in Mexico; 3) Poultry industry become potentialin domestic and foreign market; 4) Mexico became ambitious to make theirpoultry industries competing in international trades; and 5) the pressure ofdomestic industries to Mexico governmentKeywords: Anti-dumping, Chicken Leg Quarters, Mexico â U.S trade.